2017
DOI: 10.1002/adfm.201703006
|View full text |Cite
|
Sign up to set email alerts
|

From Molecular‐Level Organization to Nanoscale Positioning: Synergetic Ligand Effect on the Synthesis of Hybrid Nanostructures

Abstract: A key challenge in advancing the design of hybrid nanostructures (HNs) lies in the difficulty in mastering the principle of selected hybrid formation, which is complicated not only by the size and shape variations of nanoparticles but also by the interfacial phenomena associated with surface ligands. Here this study elaborates the formation mechanism of HNs by a combined experimental and theoretical study employing multiscale simulations and shows how molecular information encoded on particle surface can be tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 97 publications
1
11
0
Order By: Relevance
“…In our previous work, we showed that a possible phase separation of SC and TA on the surface of Ag NPs may exist as confirmed by molecular dynamics simulations. [5] Here we postulate that similar phenomena may occur here considering both the metallic nature of Au and Ag NPs and their comparable surface structures. [51] We investigate such possible phase separation by photoluminescence (PL) spectra thanks to the emission properties of TA.…”
Section: Resultssupporting
confidence: 68%
See 2 more Smart Citations
“…In our previous work, we showed that a possible phase separation of SC and TA on the surface of Ag NPs may exist as confirmed by molecular dynamics simulations. [5] Here we postulate that similar phenomena may occur here considering both the metallic nature of Au and Ag NPs and their comparable surface structures. [51] We investigate such possible phase separation by photoluminescence (PL) spectra thanks to the emission properties of TA.…”
Section: Resultssupporting
confidence: 68%
“…Such ligand combination ensures the synthesis of uniformly small sized Au NPs, similar with our previous work on the synthesis of Ag NPs. [ 5 ] Raman spectroscopy is used to confirm the presence of TA as a competitive ligand for Au NPs (Figure 1b). Compared with SC‐Au, Au NPs synthesized by using both SC and TA (SC,TA‐Au) show multiple characteristic peaks centered around 1599, 1584, 1529, 470, 432 and 395 cm –1 that can be associated with aromatic stretching, deformation, torsion and bending.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent, alternative approach to achieve specificity is the incorporation of defined chemical interactions between molecules on the surface of the particles. For example, Xiang et al directed the formation of metal–semiconductor heterodimers by changing the composition of the citric/gallic acid ligand layer . Click chemistry has been used to connect Janus particles into linear assemblies .…”
Section: Discussionmentioning
confidence: 99%
“…From the viewpoint of polymer chemistry, transesterification, 3−5 Diels−Alder reactions, 6,7 and condensation 8 are commonly used for the synthesis of the thermosets. Recently, more elaborate chemical reactions have also been explored involving transcarbamoylation, 9,10 transcarbonation, 11 thiol−ene reaction, 12,13 transalkylation, 14,15 trithiocarbonate exchange, 16 boronate exchange, 17−19 and olefin metathesis. 20,21 Such polymers have been mainly introduced as vitrimers, 22 or covalent adaptable networks, 23 and have been applied to the environmental fields.…”
mentioning
confidence: 99%